Microcontroller based Delta Modulated PMW for three phase inverter - Ayu Annur Fetrah, Yusoff (2012)
One of the PWM schemes proposed for the control of inverters supplying ac drive is Delta Modulation. Presently, microcomputer has been used as an alternative to the standard Delta Modulation PWM technique. Even though the microcomputer is considered as power computing machine, their weakness is that to communicate with peripheral equipments, they must use specialized circuit added as an external chips. By utilizing the features of microcontroller, they can just fit inside other device like the inverter or other appliance and also they does not need any other specialize external component for its application. The microcontroller based delta modulated PWM for 3-phase inverter has been proposed in this project in order to get better solution for the control of inverter. The simulation of Delta Modulation techniques is carried out using PROTEUS ISIS 7.0 in order to get six modes of delta modulated PWM switching scheme. Then, the microcontroller PIC18F4550 circuitry to generate Delta PWM is assembled. The circuit from the simulation can produce the necessary Delta PWM signal to control the inverter.